Finding an Easier Way to Explain the Statement of Cash Flows - Kim, Seung Hwan (International Journal of Accounting and Financial Reporting, 2021)
The statement of cash flows is one of the required financial statements of public companies, and thus is required of all accounting majors. After learning the other required financial statements in an introductory financial accounting course and, again, in the first intermediate accounting course, accounting majors learn how to prepare the statement of cash flows in the second or last intermediate accounting course. Most accounting majors find the statement of cash flows significantly more difficult to learn than any other financial statements. Especially, students find it most difficult to understand the indirect method of preparing the statement of cash flows. Preparing the statement of cash flows using the indirect method, students go through the most difficult time, specifically, doing the adjustments that are made to net income to reconcile to cash flows from operating activities. In this paper, presented is a different way to explain the principles of indirect method of preparing the statement of cash flows with a focus on the reconciliation of net income to cash flows from operating activities. Different from the explanations in the textbooks available in the market, the approach presented in the paper is preferred by all the students who were taught the statement of cash flows. Also, pointed out in the paper are a few things that students are easily confused of in learning the statement of cash flows.